Successful treatment of fibrosing cholestatic hepatitis with pegylated interferon, ribavirin and sofosbuvir after a combined kidney–liver transplantation. (29th September 2014) - Delabaudière, Cyrielle; Lavayssière, Laurence; Dörr, Gaëlle; Muscari, Fabrice; Danjoux, Marie; Sallusto, Federico; Peron, Jean Marie; Bureau, Christophe; Rostaing, Lionel; Izopet, Jacques; Kamar, Nassim
Summary Fibrosing cholestatic hepatitis (FCH) is a classical but rare and severe form of recurrent hepatitis C virus (HCV) after liver transplantation. Classical anti‐HCV therapy, that is pegylated‐interferon (peg‐interferon) and ribavirin, has been shown to have limited efficacy in treating FCH. Herein, we report on the first case of successful use of peg‐interferon, ribavirin, plus sofosbuvir to treat HCV‐induced FCH in a combined liver–kidney transplant patient. Antiviral therapy was given for 24 weeks. HCV clearance occurred within 4 weeks after starting therapy and was maintained until 4 weeks after the end of therapy. Antiviral tolerance was good. We conclude that the use of sofosbuvir‐based anti‐HCV therapy can be successfully used to treat FCH after a liver or combined kidney–liver transplantation.